Design Of Digital Processing Techniques For WCDMA Cellular Systems - Tan, Alan Wee Chiat (2002)
Baseband processing techniques for Code Division Multiple Access (CDMA)systems generally fall into two broad categories: error coding and signal spreading. This thesis addresses both these issues in the context of a Wideband CDMA(WCDMA) baseband receiver. The Third Generation Partnership Protocol (3GPP) standard will be adopted in specifying the system model.